(untitled) (Bangladesh Journal of Pharmacology, 2015)
The aim of this study was to investigate the effects of paeonol on the expression of NF-κB pathway induced by homocysteine. After Human umbilical vein endothelial cells exposed to homocysteine for 24 hours, paeonol (0.15-0.6 mmol/L) improved the cell viability (p<0.05). NF-κB p65 mRNA expression was reduced largely (p<0.05) and IκB-α protein expression increased significantly (p<0.01). The staining of NF-κB p65 in nucleus was not as much as those in homocysteine injured model group (p<0.01). Therefore, paeonol can inhibit IκB-α protein degradation and suppress NF-κB transferred into nuclear in order to inhibit the activation of NF-κB.